3D Body Data Analysis of Women’s Top Sizes Aged 18-25 Years (Journal of Fiber Bioengineering and Informatics, 2024)
Few studies in China use age as a criterion for garment size analysis in female body shape research. Thisproject addresses the challenge of designing clothing that fits young women aged 18-25 by examiningtheir upper body shapes. Combining Martin measurements and three-dimensional scanning, data on198 women’s body characteristics were collected, and morphological changes in their upper bodies wereanalysed.The upper body shapes were categorised into four types, and representative silhouettes were compared.The body shape classification results were combined with the national chest-waist difference classificationmethod. The primary control variables for women’s shirt sizing were determined, and a linear regressionequation was used to obtain the segmented values for each control variable.Ultimately, a specification system for women’s shirt sizes was established, providing a novel approachto research on body types and sizing systems.